SAVINGS OF THE ROMANIAN HOUSEHOLDS – RECENT ASPECTS IN THE CONTEXT OF THE WORLD FINANCIAL CRISIS - Constanţa MIHĂESCU; Ileana NICULESCU-ARON (Revista Română de Statistică, 2012)
Both theoretical models and practical experience indicate a strong relationship between savings in a country, investment levels and, implicitly, economic growth.The economic recession caused by the financial crisis diminished the saving potential at national level in most EU member states. Economic recovery requires investments, population savings being an important source for their financing.Consequently, the analysis of the trends regarding population savings, knowledge about the determinant factors and saving behaviour is of special importance for the economic policy makers.The first part of the present paper analyzes savings evolution in Romania after 1989, followed by the identification of the main determinants of households’ savings based on the Household Budget Survey data.